Zmiany systemu edukacji menedżerów podstawą sukcesu przedsiębiorstw - Skłodowski, Henryk (Changes of managers' educational system - the basis of enterprises' success, 2006)
Knowledge, social skills, habits, motivation, attitudes, aptitudes and employees’ behaviour are the basis of competition between enterprises as well as competition among employees. Knowledge acquired during study (concerning practical skills and social skills) is extremely important in a future job. Nowadays, manager’s post requires wide (interdisciplinary) knowledge. To be effective in management it is necessary to understand human nature – it allows developing creativity and initiative. The real power of a manager manifests in abilities to develop initiative and creativity of employees and in abilities to leadership. Therefore, students should be taught, since the beginning of their study, how to be a good manager in the 21st century.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1130, s. 147-152